ANALISIS PERBEDAAN RASIO KEUANGAN BPR KONVENSIONAL DAN BPR SYARIAH (Students' Journal of Accounting and Banking, 2013)
This study aims to compare the financial risks of conventional BPR and BPR sharia during the period December 2011-June 2012 by using the bank's financial ratios. Financial ratios used consists of Capital Assets Ratio (CAR), Non Performing Loan (NPL), Return on Assets (ROA), Return on Equity (ROE), Operating Expenses Operating Income divided (BOPO), and Loan to Deposit Ratio (LDR). Based on a sample of predetermined criteria, obtained two sample groups, namely the conventional 2 RB and 2 RBs sharia. Analysis tools used to prove the hypothesis in this study is Kolmogorov-Smirnov test, independent sample t-test and Mann-Whitney test. The analysis performed shows that the average financial ratios sharia rural banks (CAR, ROA, and ROE) are significantly better than conventional BPR, while the other ratios (NPL, BOPO, and LDR) sharia BPRs lower quality. But the views of the entire Islamic rural banks showed a lower risk than conventional BPR.Keywords: financial ratios, financial risk, BPR, t-test, Mann-Whitney t-test.